2020
DOI: 10.3390/jcm9051580
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Water Content in Lean Mass as an Indicator of Muscle Quality in an Older Obese Population

Abstract: Background: In aged populations, muscle strength depends more on muscle quality than on muscle quantity, while all three are criteria for the diagnosis of sarcopenia. Intracellular water content (ICW) in lean mass (LM) has been proposed as an indicator of muscle quality related to muscle strength in older people. Objectives: To evaluate the relationship between the ICW/LM ratio, muscle strength and indicators of functional performance in obese older adults, and to assess the value of the ICW/LM ratio as an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…32 Two recent studies reinforced the idea that low-grade chronic cell dehydration might play a role in loss of muscle function; high ICW content of myocytes, independent of muscle mass, had been associated with better functional performance and a lower frailty risk in aged populations. 11,12 Goulet et al also suggested that acute dehydration of 1% of body weight in healthy 60-75 years old men could affect muscle endurance, power and strength. 33 Moreover, the correlation between ICW and muscle strength has also been observed in young adult athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Two recent studies reinforced the idea that low-grade chronic cell dehydration might play a role in loss of muscle function; high ICW content of myocytes, independent of muscle mass, had been associated with better functional performance and a lower frailty risk in aged populations. 11,12 Goulet et al also suggested that acute dehydration of 1% of body weight in healthy 60-75 years old men could affect muscle endurance, power and strength. 33 Moreover, the correlation between ICW and muscle strength has also been observed in young adult athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular water (ICW) is a biomarker of cell hydration status and muscle mass. In elderly individuals with similar muscle mass, those with lower ICW had a worse functional performance and a higher frailty risk, suggesting a harmful effect of cell dehydration, independently of muscle mass 11–13 . As with the age‐related ICW decline, ICW significantly decreases over time in HD patients.…”
Section: Introductionmentioning
confidence: 97%
“…The ICW/LM ratio is based on the hypothesis of reduced muscle cells or reduced hydration, which is plausible in the obese population. Regardless of the reason, the altered cell volume determined by ICW seems to be an important metabolic signal that regulates cell and muscle functions [11]. However, little is known about muscle quality indicators, including the ICW/LM ratio in the adult population with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The association between the amount of muscle mass and muscle strength has been made evident in the literature [8,9]. However, recent studies suggest that muscle quality, among other aspects, can better explain the decline in muscle strength levels [10,11]. Muscle quality is de ned as the capacity to generate force relative to the volume of contractile tissue [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation